The Correlation Between Reading Habits and Students’ Grammar Mastery of Simple Past Tense in Tenth Grade of Man 1 Bukittinggi in The Academic Year 2021/2022 - Messi Putri; Reflinda Reflinda (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aimed to find out whether there was any significant correlation between Reading Habits and Grammar mastery of simple past tense in the tenth grade of MAN 1 Bukittinggi In Academic Year 2021/2022 academic years 2021/2022. The design of this research was correlational research. The results of the research show that there was no correlation between students’ Reading Habits and their Grammar mastery of simple past tense in the tenth grade of MAN 1 Bukittinggi In Academic Year 2021/2022 academic years 2021/2022. The researcher found that the coefficient of correlation between students’ Reading Habits and their Grammar mastery of simple past tense in the tenth grade of MAN 1 Bukittinggi In the Academic Year 2021/2022 is 0,077.. In conclusion, the magnitude of the correlation between reading habits and Grammar mastery on simple past tenses was very low correlation. In conclusion, this research was done for finding the correlation between students’ Reading Habits and their Grammar mastery of simple past tense in the tenth grade of MAN 1 Bukittinggi In the Academic Year 2021/2022.